Application Research of Online Sensing Technology of Dynamic Capacity Increase. Issue 2 (April 2021) - Chen, Li Hui; Feng, Yang; Yuan, Fu Zhong; Ye, Cui Rong
Abstract: With the continuous development of my country's national economy, the demand for electricity in various regions continues to increase, and the operation of high-voltage overhead transmission lines in many regions is already facing transmission bottlenecks. Therefore, it is very important to study the dynamic capacity increase technology of high-voltage overhead lines. This article points out the main technologies and methods to increase the transmission capacity of transmission lines, analyzes the advantages and disadvantages of each technical method, evaluates the advantages and limitations of dynamic capacity expansion technology and economic feasibility, and finally proposes that dynamic capacity expansion technology is developing. The existing problems and the future development trend point out the broad application prospects and important practical significance of the research on the new capacity-increasing wire of the online state-aware technology.